2020
DOI: 10.1158/0008-5472.can-20-0156
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Vessels in Tumor Dissemination versus Immunotherapy

Abstract: During the growth of various cancers, primary tumors can escape antitumor immune responses of their host and eventually disseminate into distant organs. Peritumoral lymphatic vessels connect the primary tumor to lymph nodes, facilitating tumor entry into lymph nodes, systemic circulation, and metastasis. Lymph node metastases that occur frequently provide sites of tumor cell spread, whereas tumor antigen transfer into and presentation in tumor-draining lymph nodes induce activation of tumor-specific T-lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…Tumor lymphatic vessels connect primary tumor cells and lymph nodes. Consequently, cancer cells invade the lymph nodes to move to other organs [29]. In the present study, we found that TGF-β signaling is involved in lymphatic drainage, in addition to confirming structural abnormalities of lymphatic vessels by the loss of LEC-specific TGF-β signaling.…”
Section: Discussionsupporting
confidence: 78%
“…Tumor lymphatic vessels connect primary tumor cells and lymph nodes. Consequently, cancer cells invade the lymph nodes to move to other organs [29]. In the present study, we found that TGF-β signaling is involved in lymphatic drainage, in addition to confirming structural abnormalities of lymphatic vessels by the loss of LEC-specific TGF-β signaling.…”
Section: Discussionsupporting
confidence: 78%
“…During cancer progression lymphatic vessels can play dual roles (reviewed in Oliver et al, 2020 ; Petrova and Koh, 2020 ; Vaahtomeri and Alitalo, 2020 ). On the one hand, they promote tumor metastasis by providing malignant cells with an escape conduit for dissemination toward the lymph nodes and distal metastatic niches.…”
Section: Structure and Functions Of The Lymphatic Systemmentioning
confidence: 99%
“…Once the solid tumor becomes vascularized, there is a rapid switch from a dormant to a malignant state that promotes further growth and tissue dissemination ( Lugano et al, 2020 ). In addition to blood ECs, lymphatic vessels are also present in the tumor microenvironment, and are considered to play an active role in primary tumor progression, metastatic spread and immunomodulation ( Stacker et al, 2014 ; Garnier et al, 2019 ; Oliver et al, 2020 ; Petrova and Koh, 2020 ; Vaahtomeri and Alitalo, 2020 ). On the one hand, tumor-associated lymphatics uptake the interstitial fluid containing cells and macromolecules of tumor mass origin, and drain them to the sentinel lymph node.…”
Section: Formation Of Cancer-associated Lymphaticsmentioning
confidence: 99%
“…13 In addition to facilitating tumor metastasis, increased tumor-associated lymphangiogenesis may also modulate immune response as the major function of lymphatic system is to transport tumor antigens by dendritic cells to lymph nodes, presenting to T-lymphocytes and initiate adaptive immune response. 14 Therefore, lymphangiogenesis can enhance the efficacy of immunotherapy in some tumor models. However, since tumors can produce immunosuppressive molecules to attenuate anti-tumor immunity, lymphangiogenesis may still serve as a pro-metastatic function in cancer progression (Figure 1).…”
Section: Lymphatic Metastasis and Lymphangiogenesis In Cancer Progressionmentioning
confidence: 99%